Book Review: Variations in Post-Communist Europe: a Worthwhile Addition - Saar, Ellu; Unt, Marge (Studies of Transition States and Societies, 2014)
On Baltic Slovenia and Adriatic Lithuania. A Qualitative Comparative Analysis of Patterns in Post-Communist Transformation by Zenonas Norkus, 2012, Central European University Press.